Exploring the impact of virtual reality on presence: findings from a classroom experiment - Christine Austermann; Florin Blanckenburg; Korbinian Blanckenburg; Till Utesch (Frontiers in Education)
IntroductionThis study examines the perception of presence among students using virtual reality (VR) compared to iPads. The research aimed to provide deeper insights into students' immersive experiences and identify factors influencing perceived presence.Method and resultsUsing a comparative approach, we show a significant difference between the two groups, with students using VR reporting a heightened sense of immersion. Additionally, participant's previous experience with immersive VR affect the presence significantly, while we report no detectable effects of age and gender.DiscussionThese findings contribute to the discussion on innovative teaching methods, supporting the development of more effective and inclusive virtual learning environments.